Traditional embroidery revival for sustainability: a systematic literature review and bibliometric analysis - Neetu Singh; Madhuri Singh (Discover Sustainability)
Abstract This study investigates the revival of traditional embroidery crafts within the context of sustainability, addressing a critical gap in the existing literature. Employing a hybrid methodology that integrates the PRISMA framework and systematic literature review with bibliometric analysis via VOSviewer software, we meticulously examine 4379 papers published from 2004 to 2024 in the Scopus database. Our analysis reveals four distinct clusters through co-word analysis, each illuminating different dimensions of embroidery craft revival. We synthesize these findings to identify key themes and develop actionable propositions that inform best practices for enhancing sustainability in this artisanal domain. The results underscore a significant need for more research focused on practice-led approaches, emphasizing the importance of integrating contemporary methodologies with traditional techniques. By offering recommendations to bolster the existing knowledge framework, this paper aims to contribute to the sustainable revitalization of embroidery crafts, fostering greater cultural appreciation and economic viability for artisans worldwide.